2021
DOI: 10.1177/2399369321992776
|View full text |Cite
|
Sign up to set email alerts
|

A case of pembrolizumab induced distal renal tubular acidosis

Abstract: Immunotherapy has become a mainstay therapeutic in a variety of malignancies. Checkpoint inhibitors are used to enhance the endogenous immune response to target malignancy. The primary targets of checkpoint inhibitors include programed cell death receptor 1 (PD-1), programed cell death ligand 1 (PD-L1), and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4). Despite clinical benefits, immune checkpoint inhibitors are associated with side effects termed immune-related adverse events (irAEs). We report a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In some cases distal renal tubular acidosis can persist despite improvement of kidney function, while tapering corticosteroid therapy. 27,28 In these cases, analysis of the kidney biopsies by immunofluorescent labeling with specific antibodies shows loss of intercalated cells expressing anion exchanger type 1 (AE1) and B1 and α4 subunits of vacuolar-type H⁺ -ATPase (V-ATPase) as compared to controls, elucidating in part the mechanism of autoimmunity. 28…”
Section: Patterns Of Kidney Injurymentioning
confidence: 99%
“…In some cases distal renal tubular acidosis can persist despite improvement of kidney function, while tapering corticosteroid therapy. 27,28 In these cases, analysis of the kidney biopsies by immunofluorescent labeling with specific antibodies shows loss of intercalated cells expressing anion exchanger type 1 (AE1) and B1 and α4 subunits of vacuolar-type H⁺ -ATPase (V-ATPase) as compared to controls, elucidating in part the mechanism of autoimmunity. 28…”
Section: Patterns Of Kidney Injurymentioning
confidence: 99%
“…Overall, all these studies reported a total of six cases of RTA in patients who received immune checkpoint inhibitor (Table 2). 5,[8][9][10] Here we report another case of distal RTA as a side effect of an immune checkpoint inhibitor. The mechanism by which distal RTA develops in patients who received immune checkpoint inhibitor is not clearly known.…”
Section: Discussionmentioning
confidence: 79%
“…16 With extensive use of the current available immune checkpoint inhibitors and potential availability of new ones in the near future, we should potentially expect to see more kidney side effects with different pathologies because of immune checkpoint inhibitors. 9 60 years old male Lung adenocarcinoma Pembrolizumab 70 years old male Melanoma Nivolumab 80 years old male Renal cell carcinoma Nivolumab Charmetant et al 5 59 years old male Bronchopulmonary Nivolumab and Pembrolizumab Atiq et al 10 74 years old male Melanoma Pembrolizumab…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only few case reports and case series thus far describing this phenomenon. [2][3][4][5] However, distal RTA being an immune-mediated phenomenon is not a novel concept, as there are a range of autoimmune diseases that have been associated with distal RTA. Distal RTA is also perhaps an underdiagnosed disease among patients receiving immune checkpoint inhibitors, as it is typically asymptomatic and associated with concurrent decreased kidney function.…”
Section: Quizmentioning
confidence: 99%